Falco peregrinus Tunstall 1771 - Castro-Vargas, Fernando; Cruz-Mendivelso, Yerson; Ortega-Chamorro, Darwin; Palacino-Rodríguez, Fredy (Zenodo, 2020)
Falco peregrinus Tunstall, 1771 Figure 7D New records. Lonely individuals and couples have been seen perching and feeding on doves and pigeons in a replica building of the Taj Mahal. We recorded this species systematically between October 2018 and April 2019. Identification. Dorsal region of the body is dark blue– grey, with the crown, nape and broad legs under the eye black. Atrial region, lateral areas and lower parts of the neck are white. Chest and belly in brown are barred, with brown tailed tail, grey blue and greyish white. Head sides, including black ears. Remarks. We did not record any reproductive events. This species is a boreal migratory bird. It is a winter resident scarce in the Bogotá Savannah (ABO 2000). Geographic distribution. Western North America, Central and South America. : Published as part of Castro-Vargas, Fernando, Cruz-Mendivelso, Yerson, Ortega-Chamorro, Darwin & Palacino-Rodríguez, Fredy, 2020, Birds from northeastern Bogotá Savannah, Cundinamarca, Colombia, pp. 1375-1391 in Check List 16 (5) on pages 1385-1386, DOI: 10.15560/16.5.1375 : {"references": ["ABO (Asociacion Bogotana de Ornitologia) (2000) Aves de la Sabana de Bogota. Guia de campo. Quebecor Impreandes, Bogota, 276 pp."]}